Polycyclic Aromatic Hydrocarbon (PAH) Content and Microbiological Investigation of Dried Fig Fruits in Tikrit City - Hameed, Ayat Munaf (American Journal of Biology and Natural Sciences, 2026)
Human, industrial or agricultural activities or microorganisms from dried fruits generate a variety of pollutants such as polycyclic aromatic hydrocarbons (PAHs) in food products, particularly in dried fruits sold in local markets. This study sought to quantify the amount of polycyclic aromatic hydrocarbons in dried fruits as well as isolate and identify the microorganisms (bacteria). The study outcomes revealed that most dried fruits contain PAHs, which are a result of vehicle exhaust, old processing techniques and the remains of oil refineries and power plants. Moreover, the present study revealed that Escherichia coli was the predominant amongst the types of bacteria present in dried figs followed by Staphylococcus and Pseudomonas aeruginosa.